Enhancing Specificity, Precision, Accessibility, Flexibility, and Safety to Overcome Traditional CRISPR/Cas Editing Challenges and Shape Future Innovations - Muna Alariqi; Mohamed Ramadan; Lu Yu; Fengjiao Hui; Amjad Hussain; Xiaofeng Zhou; Yu Yu; Xianlong Zhang; Shuangxia Jin (Advanced Science)
Abstract Derived from the bacterial immune system, CRISPR/Cas9 induces DSBs at specific DNA sequences, which are repaired by the cell's endogenous mechanisms, leading to gene insertions, deletions, or substitutions. Despite its transformative potential, several challenges remain in optimizing of CRISPR/Cas systems, including off‐target effects, delivery methods, PAM restrictions, and the limitations of traditional editing approaches. This review focuses on the interplay between these challenges and their contributions to gene editing precision, specificity, accessibility, flexibility, and safety. How reducing off‐target effects enhances specificity and safety is explored, while discussing the role of HDR‐based editing in achieving precise gene modifications, alongside alternative methods such as base editing and prime editing. Improved delivery mechanisms are examined for their impact on accessibility and efficiency, while the reduction of PAM restrictions is highlighted for its contributions to flexibility. Lastly, emerging cleavage‐free editing technologies are evaluated as they relate to safety and accessibility. This focused review aims to clarify the connections among these aspects and outline future research directions for advancing CRISPR‐based applications.